Long-term survival with anlotinib as a front-line treatment in an elderly NSCLC patient: A case report - Jingyi Wang; Xiaoqing Li; Juan Zhou; Dan Qiu; Mengyao Zhang; Lan Sun; Shengwen Calvin Li; Shengwen Calvin Li (Frontiers in Oncology, 2023)
BackgroundHalf of the population of non-small cell lung cancer (NSCLC) patients are older than 70 years and have limited therapeutic options due to poor tolerance and being excluded in most clinical trials. Anlotinib hydrochloride, a novel oral multi-target tyrosine kinase inhibitor, has been approved for the standard third-line treatment for NSCLC in China. Herein we report an elderly NSCLC patient without any driver gene mutations who was undergoing anlotinib as a front-line treatment and who achieved long-term survival.Case summaryThe 77-year-old male patient was admitted to the hospital for chest tightness after engaging in physical activity for a week. The patient has been diagnosed with stage IIIB driver gene-negative squamous cell lung carcinoma. After that, he was treated with anlotinib for 2 years and 10 months from the first diagnosis until the last disease progression. Briefly, anlotinib combined with platinum-based chemotherapy was performed as the first-line therapy over six cycles. After 6 more cycles of anlotinib monotherapy maintenance, disease progression occurred. Then, anlotinib combined with tegafur was administered as a salvage treatment, and the disease was controlled again. After 29 cycles of anlotinib combined with tegafur regimens, the disease progressed finally. The patient achieved a total of 34 months of progression-free survival after anlotinib was used as the front-line treatment. He is still alive with a good performance status now (performance status score: 1).ConclusionThis patient achieved long-term survival using anlotinib as a front-line regimen combined with chemotherapy.